2015
DOI: 10.1017/s0021859614001105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of culm morphology, anatomy and chemical composition of foxtail millet cultivars differing in lodging resistance

Abstract: Lodging can be an important factor in limiting yield and quality of summer foxtail millet [Setaria italica (L.) P. Beauv.]. Although lodging resistance varies among different genotypes, direct selection for lodging resistance is difficult because of its sporadic occurrence in the field and inconsistency between years. A 2-year-field study was conducted with 35 summer foxtail millet cultivars or advanced breeding lines to determine the association between lodging resistance and culm morphology, anatomy and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Plant density and N application have significant effects on culm development. Vascular bundle number (NVB) and area (AVB) are the major anatomical features influencing stem-breaking strength and transportation (Tian et al, 2015). We found that whereas increasing plant density significantly decreased NVB and AVB at the first internode, an increase in N application increased NVB and AVB, and GN and yield per spike also increased with excessive N application, Moreover, the results of correlation analysis indicated that the number vascular bundle was significantly positively correlated with yield per spike, and that vascular bundle area was significantly positively correlated with grain filling rate.…”
Section: Discussionmentioning
confidence: 99%
“…Plant density and N application have significant effects on culm development. Vascular bundle number (NVB) and area (AVB) are the major anatomical features influencing stem-breaking strength and transportation (Tian et al, 2015). We found that whereas increasing plant density significantly decreased NVB and AVB at the first internode, an increase in N application increased NVB and AVB, and GN and yield per spike also increased with excessive N application, Moreover, the results of correlation analysis indicated that the number vascular bundle was significantly positively correlated with yield per spike, and that vascular bundle area was significantly positively correlated with grain filling rate.…”
Section: Discussionmentioning
confidence: 99%
“…Stalk lodging in maize was positively correlated with basal internode length (Esechie, 1985), but negatively correlated with basal internode diameter (Martin and Russell, 1984;Novacek et al, 2013). The lodging coefficient of the stem in foxtail millet was associated with specific morphological properties of the culm, such as greater culm diameter, culm wall thickness (Tian et al, 2015). Wang et al (2006Wang et al ( , 2012 reported that the most important anatomical and chemical properties for selection of lodging-resistant wheat cultivars were the ratio of culm wall thickness to the outer radius.…”
Section: Discussionmentioning
confidence: 99%
“…Lodging causes poor grain filling and yield loss, reduces grain quality, and reduces mechanical harvesting efficiency (Acreche and Slafer, 2011; Berry and Spink, 2012). Much research has been carried out on the external form, internal structure, chemical composition and mechanical strength of cereal crops and how this affects lodging (Esechie, 1985; Luo et al , 2007; Kong et al , 2013; Novacek et al ., 2013; Tian et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lodging is one of the main factors that limits cereal yield and seriously affects the mechanical harvesting efficiency (Berry especially the strength of the basal internodes (Liu, Ma, Zhao, & Zhou, 2018;Zuber et al, 1999). The strength of the internode of crop stems is mainly determined by their morphological traits and anatomical structure (Tian et al, 2015;Zhang et al, 2016). Previous studies have shown that in terms of phenotype, crops have slender stems, long internodes, and poor lodging resistance (Liu et al, 2018;Nomura et al, 2019;Weng et al, 2017;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%